If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 0.5y = -2 Solving 3x + 0.5y = -2 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.5y' to each side of the equation. 3x + 0.5y + -0.5y = -2 + -0.5y Combine like terms: 0.5y + -0.5y = 0.0 3x + 0.0 = -2 + -0.5y 3x = -2 + -0.5y Divide each side by '3'. x = -0.6666666667 + -0.1666666667y Simplifying x = -0.6666666667 + -0.1666666667y
| -108*3.14=6*3.14 | | 9-c=10 | | Y=11x^2+7 | | x+(x(.05))=63 | | 7(x-1)-2(x+1)=4x+5(2x-5) | | 5n+11=48 | | -13m+9m+-1=15 | | 85=-3x+4(5x-17) | | Y=11x^2*7 | | 3x+2y+5x+6y= | | -3x-3(-5x+10)=54 | | -4x-2(8x+1)=-(20x-10) | | 3+y=2x-3 | | 20-2x=2x+5 | | 2-0.7p-0.75=0.3p | | -0.7x=-6.3 | | 3(3.66+0.66y)-2y=11 | | 5p-4p+1=17 | | -114=4x-6(-2x-5) | | -63x+15=-48 | | 14.6-1.83= | | 14s-13s=14 | | 4cos*3x+7=6 | | 9x+45=4x | | 15e-3=20e+17 | | 5x-4(2x-18)=99 | | 5y-4y-1=17 | | -3-y=5wz+16 | | -9h+10=118 | | -97=5x-3(4x+16) | | 3x-13x=10 | | 2t+24-12t-3=14 |